Aligning Learning & Development Strategy with Business: Strategy to Operations. (December 2014) - Panda, Abinash; Karve, Swati; Mohapatra, Dilip
This research note presents the current challenges for the learning leaders in India, and what they should do to ensure that learning function is treated as a strategic function by the business leaders. The need is to align learning function with the business, assessing the current level of organizational capabilities vis-à-vis what is needed now and in the future to remain competitive. Such assessment helps to identify the capability gaps, which should be bridged through developmental interventions, conceptualized and executed by the Learning & Development function. Execution is vital for this as most often well-crafted strategy goes awry, if not properly executed. A template to operationalize Learning & Development strategy is also discussed in this article.